Concentrating solar power technology in Bangladesh: Potential and challenges for large-scale implementation - Md. Abdu Rabbir Rasul; Nafeem Yasar; Nahid-Ur-Rahman Chowdhury (Energy Conversion and Management: X)
This study outlines the possibilities and barriers to implementing concentrating solar power (CSP) technology in Bangladesh by conducting a techno-economic feasibility analysis of three distinct technologies of CSP plants in five different locations throughout the country. Utilizing the System Advisor Model (SAM) software, a thorough analysis of the technical and economic aspects of implementing a 50 MW Parabolic Trough CSP Plant, Linear Fresnel CSP Plant, and the Solar Power Tower CSP Plant in the districts of Munshiganj, Sunamganj, Dinajpur, Cox’s Bazar, and Pabna was conducted. The sites were chosen based on factors such as the availability of nearby hydrological assets, the district’s average Direct Normal Irradiance (DNI), etc. These criteria were comprehensively met, and the average DNI of 1900–2100 kWh/m2 was a crucial parameter in the simulation studies. From a technical aspect, keeping an average Thermal Energy Storage (TES) of 6 h, the Capacity Factor (CF%) and for economic feasibility, the Levelized Cost of Energy (LCOE) and Net Present Value (NPV) were optimized to determine the best possible blueprint. It is observed that in terms of LCOE, NPV, and CF%, the ideal technology to be implemented in Bangladesh would be the Power Tower-Molten Salt technology, as it ensures an LCOE as low as $0.1251/kWh in Dinajpur, NPV as high as $40,880,084 in Cox’s Bazar, and CF% as high as 48.3 % in Dinajpur. These findings clearly stipulate the potential for CSP technology in Bangladesh’s energy landscape and how it can replace or hybridize conventional power generation techniques.